214k views
1 vote
HELPP!!!! 100 points. Which expression is equivalent

HELPP!!!! 100 points. Which expression is equivalent-example-1
User Notytony
by
5.0k points

1 Answer

6 votes

Answer:


\textsf{A.} \quad 2x√(11x)

Explanation:

Given expression:


2x√(44x)-2√(11x^3), \;\; \text{if $x > 0$}

Rewrite 44 as 4 · 11:


\implies 2x√(4 \cdot 11x)-2√(11x^3)

Rewrite the exponent 3 as 2+1:


\implies 2x√(4 \cdot 11x)-2\sqrt{11x^(2+1)}


\textsf{Apply exponent rule} \quad a^(b+c)=a^b \cdot a^c:


\implies 2x√(4 \cdot 11x)-2√(11x^2x)}


\implies 2x√(4 \cdot 11x)-2√(x^2 \cdot 11x)}


\textsf{Apply radical rule} \quad √(ab)=√(a)√(b):


\implies 2x√(4)√(11x)-2√(x^2)√(11x)

Rewrite 4 as 2²:


\implies 2x√(2^2)√(11x)-2√(x^2)√(11x)


\textsf{Apply radical rule} \quad √(a^2)=a, \quad a \geq 0:


\implies 2x \cdot 2√(11x)-2x√(11x)

Simplify:


\implies 4x√(11x)-2x√(11x)


\implies 2x√(11x)

User Lima
by
5.7k points